Effects of the FR 4 Substrate Realized in a Circularly Polarized UHF-RFID Reader Antenna with Fractal Geometry for Enhancing Parameters - Chitra Varadhan; S. Arulselvi; Fekadu Ashine Chamatu (Advances in Materials Science and Engineering)
The proposed RFID reader antenna progressed with perfect electric conductor (PEC) as the radiating element and FR 4 as the substrate to achieve circular polarization, enhancement in bandwidth, and read range. The design presents a CPW feed RFID antenna for near-field reading applications, between the range of 903 MHz to 929 MHz. The operating frequency of the proposed design is 900 MHz, axial ratio of the model is less than 3 dB, impedance bandwidth is 256 MHz, and axial bandwidth is 36 MHz, proving to be adequate for near-field RFID reader applications such as item-level tagging and smart shelf. The proposed antenna model is realized with fractal structure to achieve miniaturization. The developed antenna is optimized using EM software for numerical analysis. The designed antenna is fabricated, and the prototype is characterized in terms of dielectric constant and loss tangent. The obtained results indicate high correlation with simulation results.